2022
DOI: 10.3389/fimmu.2022.799988
|View full text |Cite
|
Sign up to set email alerts
|

Associations of HER2 Mutation With Immune-Related Features and Immunotherapy Outcomes in Solid Tumors

Abstract: BackgroundHER2 is one of the most extensively studied oncogenes in solid tumors. However, the association between tumor microenvironment (TME) and HER2 mutation remains elusive, and there are no specific therapies for HER2-mutated tumors. Immune checkpoint inhibitors (ICIs) have been approved for some tumor subgroups that lack targeted therapies, while their effects are still unclear in HER2-mutated tumors. We examined whether HER2 mutation impacts treatment outcomes of ICIs in solid tumors via its association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The ErbB2 amplification subgroup displayed increased ErbB2 protein expression, a higher abundance of tumor-infiltrating regulatory T cells, and a lower abundance of activated NK cells and CD8+ T cells compared to the standard ErbB2 control, according to the analysis of the Cancer Genome Atlas pan-cancer cohort data. [ 15 ] Some preclinical and clinical investigations have revealed that Treg cells may impair individual immune surveillance against cancer, delay cancer patients from acquiring efficient antitumor immunity, and improve tumor growth. [ 16 ] PD-1 blockade promotes the recovery of malfunctioning PD-1+/CD8+ T cells and improves PD-1 + Treg cell–mediated immunosuppression, which might explain how immunotherapy benefits ErbB2 amplification patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ErbB2 amplification subgroup displayed increased ErbB2 protein expression, a higher abundance of tumor-infiltrating regulatory T cells, and a lower abundance of activated NK cells and CD8+ T cells compared to the standard ErbB2 control, according to the analysis of the Cancer Genome Atlas pan-cancer cohort data. [ 15 ] Some preclinical and clinical investigations have revealed that Treg cells may impair individual immune surveillance against cancer, delay cancer patients from acquiring efficient antitumor immunity, and improve tumor growth. [ 16 ] PD-1 blockade promotes the recovery of malfunctioning PD-1+/CD8+ T cells and improves PD-1 + Treg cell–mediated immunosuppression, which might explain how immunotherapy benefits ErbB2 amplification patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al ( 26 ) showed that trastuzumab can upregulate PD-L1 in HER2-amplified GC cells by interacting with NK cells through the secretion of IFN-γ. Altogether, there is a complex regulatory network between HER2 and PD-L1 expression, which is not only affected by the tumor cells themselves, but also closely related to the TME ( 36 ). The relationship between molecular subtypes of GC and PD-L1, HER2 and combined HER2 and PD-L1 expression, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Data from other cohorts have been previously published and were acquired and preprocessed as described elsewhere. 19 , 20 Immune-associated indices, including tumor mutation burden (TMB), tumor neoantigen burden (TNB), microsatellite instability (MSI), and immune subtype, have been previously defined and determined. 19 , 20 , 23 …”
Section: Methodsmentioning
confidence: 99%
“… 19 , 20 Immune-associated indices, including tumor mutation burden (TMB), tumor neoantigen burden (TNB), microsatellite instability (MSI), and immune subtype, have been previously defined and determined. 19 , 20 , 23 …”
Section: Methodsmentioning
confidence: 99%